Rose: an island of stereotypes on Lost (Significação: Journal of Audiovisual Culture, 2013)
This paper is the result of research made on Geifec and has as a goal to analyze the modes of representation of the character Rose Nadler, from the American series Lost. Woman, African-American, close to 60s, overweight, Rose is in the intersection of a series of minority groups and her presence occurs as an overlapping of unusual stereotypes in the series. The theoretical references use the contributions of Mazzara (1998) and Mittell (2010) and the methodology takes the apparitions of the character in the first three seasons of the series, with images and dialogues transcriptions.